Inhibitory effects of psoralen plus ultraviolet irradiation on human leukemic cell lines - ZH Lu; YC Yang; SY Shen; WQ Tan (Acta Pharmacologica Sinica, 2017)
Inhibitory effects of psoralen plus ultraviolet irradiation on human leukemic cell lines